Interpretare e raffigurare la natura. Charles Darwin e la vita delle piante - Giaculli, Fiorella (Filosofia, 2019)
The following essay aims to illustrate that Charles Darwin’s botanical researches are pivotal not only for botany itself, but especially for the interpretation of the whole nature. The life of plants, and not only the life of animals, shows Darwin principles and phenomena such as variation, natural selection and struggle for life. Moreover, the life of plants reveals aspects similar to the life of animals: for instance, the reproduction, the movement, some biochemical elements, a certain kind of perception, the evaluation, the discernment. These traits can be considered as a proof of the theory of common descent with modification, which affirms the unity of life through the diversity of living beings. On the one hand, the life of plants helps Darwin to understand nature, while on the other hand it represents the whole nature, whose living beings are “all netted together”. Therefore, to symbolize nature, Darwin draws a tree, the tree of life.